تحليل الفعل الماضي والمضارع والأمر في جزء الثلاثين من القرآن الكريم - Wawansyah Putra Sambo, Wawansyah; Muhammad Ritonga, Ade; Fakhrurozzi, Fakhrurozzi (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
The formulation of the problem in this study is as follows: How Many Madhi, Mudhori' and Amr verses are there in Juz 30 of the Qur'an? What are the types of verses in terms of authenticity and mu'tal in juz 30 of the Qur'an? The purpose of this study is to determine the number of Madhi, Mudhori' and amr verves an what are their types in juz 30. The method used js Qualitative research with literature review. And the method used is to read references related to the study. This Study Show that in the Qur'an Especially Juz 30, there are Bery many verves. Then the researcher found that there were 558 verves with a note that were 319 madhi verves and 212 Mudhoriq verves and 27 amr verves. As for the verves in terms of their types, there were 290 authentic verves with a note that 233 were salim, 31 were mahmuz and 31 were mudhoaf, Meanwhile there are 248 mu'tal verbs of which 16 are mitsal, 84 are ajwaf, 134 are naqhis and 14 are lafif.